CRITICAL EXAMINATION ON THE MECHANISM OF APPLICATION SUBMISSION FOR LEGAL ASSISTANCE BUDGETING IN INDUSTRIAL RELATION DISPUTES - Agisa Tri Handias; Nabitatus Sa'adah (Diponegoro Law Review, 2021)
Imbalances and difficulties when workers experience industrial disputes bring out possibility of defeat in the trial. So the Government has an obligation to fight for justice by providing the budget for legal aid derived from the state budget and allocated to the budget of the Ministry of Law and Human rights. The research method used is normative, which is research that sees the effectiveness of prevailing laws. The results showed that the provision of legal aid budgets hasn’t been able to run optimally because government hasn’t provided a forum for applying legal aid budgets to legal remedies of cassation in Industrial disputes.